Acyltransferase skinny hedgehog regulates TGFβ-dependent fibroblast activation in SSc - Liang, Ruifang; Kagwiria, Rosebeth; Zehender, Ariella; Dees, Clara; Bergmann, Christina; Krasowska, Dorota; Michalska-Jakubus, Małgorzata; Kreuter, Alexander; Kraner, Max; Schett, Georg; Distler, Jörg; Ramming, Andreas (Annals of the Rheumatic Diseases, 2019)
Objectives: Systemic sclerosis (SSc) is characterised by aberrant hedgehog signalling in fibrotic tissues. The hedgehog acyltransferase (HHAT) skinny hedgehog catalyses the attachment of palmitate onto sonic hedgehog (SHH). Palmitoylation of SHH is required for multimerisation of SHH proteins, which is thought to promote long-range, endocrine hedgehog signalling. The aim of this study was to evaluate the role of HHAT in the pathogenesis of SSc. Methods: Expression of HHAT was analysed by real-time polymerase chain reaction(RT-PCR), immunofluorescence and histomorphometry. The effects of HHAT knockdown were analysed by reporter assays, target gene studies and quantification of collagen release and myofibroblast differentiation in cultured human fibroblasts and in two mouse models. Results: The expression of HHAT was upregulated in dermal fibroblasts of patients with SSc in a transforming growth factor-β (TGFβ)/SMAD-dependent manner. Knockdown of HHAT reduced TGFβ-induced hedgehog signalling as well as myofibroblast differentiation and collagen release in human dermal fibroblasts. Knockdown of HHAT in the skin of mice ameliorated bleomycin-induced and topoisomerase-induced skin fibrosis. Conclusion: HHAT is regulated in SSc in a TGFβ-dependent manner and in turn stimulates TGFβ-induced long-range hedgehog signalling to promote fibroblast activation and tissue fibrosis. Targeting of HHAT might be a novel approach to more selectively interfere with the profibrotic effects of long-range hedgehog signalling.
CRIS-Team Scopus Importer:2019-06-21
Keywords: dermal fibrosis; hedgehog signaling; skinny hedgehog; systemic sclerosis; TGFβ